Halophilic Carotenoids and Breast Cancer: From Salt Marshes to Biomedicine - Micaela Giani (MDPI AG, 2021)
Breast cancer is the leading cause of death among women worldwide. Over the years, oxidative stress has been linked to the onset and progression of cancer. In addition to the classical histological classification, breast carcinomas are classified into phenotypes according to hormone receptors (estrogen receptor—RE—/progesterone receptor—PR) and growth factor receptor (human epidermal growth factor receptor—HER2) expression. Luminal tumors (ER/PR-positive/HER2-negative) are present in older patients with a better outcome. However, patients with HER2-positive or triple-negative breast cancer (TNBC) (ER/PR/HER2-negative) subtypes still represent highly aggressive behavior, metastasis, poor prognosis, and drug resistance. Therefore, new alternative therapies have become an urgent clinical need. In recent years, anticancer agents based on natural products have been receiving huge interest. In particular, carotenoids are natural compounds present in fruits and vegetables, but algae, bacteria, and archaea also produce them. The antioxidant properties of carotenoids have been studied during the last years due to their potential in preventing and treating multiple diseases, including cancer. Although the effect of carotenoids on breast cancer during in vitro and in vivo studies is promising, clinical trials are still inconclusive. The haloarchaeal carotenoid bacterioruberin holds great promise to the future of biomedicine due to its particular structure, and antioxidant activity. However, much work remains to be performed to draw firm conclusions. This review summarizes the current knowledge on pre-clinical and clinical analysis on the use of carotenoids as chemopreventive and chemotherapeutic agents in breast cancer, highlighting the most recent results regarding the use of bacterioruberin from haloarchaea.